Maryja matka Chrystusa w świetle tekstów Starego Testamentu - Homerski, Józef (The Biblical Annals, 2017)
Only three Old Testament texts can be referred to Mary as the Mother of Jesus Christ: Gn. 3,15 in the fuller sense, Is. 7,14 and Mi. 5, 2 in the literal sense. Similarities and associations with persons, events and objects of worship appearing in the Old Testament are applied to the Virgin first of all in the Church’s liturgy.